Lesões cervicais não cariosas: prevalência, severidade e correlação com fatores etiológicos - Silva, Fernanda Martins Leão e (2006)
This study had the aim to identify the presence and the severity of noncarious cervical lesions (NCLs) and correlate them to the occurrence of premature dental contacts and to the risk factors involved in this development. There had been evaluated 66 patients of both genders, with age between 15 and 70 years, involving 1,863 teeth, which had been examined in accordance with criteria for identification of NCLs, wear facets and occlusals prematurities. The individuals had answered to the questionnaire related to the age, gender, gastrointestinal problems, medication use, dentin hypersensitiveness, diet and parafunctional habits. The evaluation of wear facets was achieved by means of visual inspection of the occlusal and incisal faces of teeth. In the identification of cervical lesions, the vestibular and lingual or palatine faces of teeth had been examined with periodontal probing located parallel to the long axis of the tooth. The teeth with NCLs had been evaluated as regards the severity, using the tooth wear index (TWI), and later examined with relation to the occlusion in centric relation (CR), maximal habitual intercuspation (MHI) and in the excursion movements. Two thirds of the individuals had presented the total of 273 cervical lesions. As regards to the distribution of lesions for group of teeth, the premolars had presented greater frequency, followed for molars and the incisors and canines with lesser frequency. The same trend was observed for wear facets. It had positive correlation between the presence of NCLs and the occlusals prematurities. For the data gotten with questionnaire, the Chi-Square test (α=.05) demonstrated difference between the individuals with and without lesion for age, parafunctional habit and dentin hypersensitiveness. The most frequent TWI was which lesions had less than 1 mm. When analyzing the risk factors involved in noncarious cervical lesions, suggest the parafunctionals habits and occlusals prematurities as the etiology agents with greater potential to develop them.